2017
DOI: 10.1016/j.bcp.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peptide transporter 2 (PEPT2) on the distribution of cefadroxil in mouse brain: A microdialysis study

Abstract: Peptide transporter 2 (PEPT2) is a high-affinity low-capacity transporter belonging to the proton-coupled oligopeptide transporter family. Although many aspects of PEPT2 structure-function are known, including its localization in choroid plexus and neurons, its regional activity in brain, especially extracellular fluid (ECF), is uncertain. In this study, the pharmacokinetics and regional brain distribution of cefadroxil, a β-lactam antibiotic and PEPT2 substrate, were investigated in wildtype and Pept2 null mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 54 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Hitherto, no influx carrier mechanism for peptide transport into brain parenchyma across the BBB has been elucidated. However, it has been reported that PepT2, expressed in the apical membrane of choroid plexus epithelial cells and plasma membrane of neural cells is involved in the removal of peptidic substrates from the CSF 32 . In this study, a significant reduction in the uptake of Gly-Sar by co-perfusion of His, a favorable PHT1 substrate 5 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, no influx carrier mechanism for peptide transport into brain parenchyma across the BBB has been elucidated. However, it has been reported that PepT2, expressed in the apical membrane of choroid plexus epithelial cells and plasma membrane of neural cells is involved in the removal of peptidic substrates from the CSF 32 . In this study, a significant reduction in the uptake of Gly-Sar by co-perfusion of His, a favorable PHT1 substrate 5 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the unbound drug concentration in brain ECF rather than total concentration of drug in brain tissue is more relevant in understanding drug transport across BBB because the total concentration of drug is confounded by ECF-ICF and/or nonspecific binding equilibration (as characterized by V u,brain and f u,brain ). The conclusion about BBB transport based on total drug concentrations in brain could therefore be misleading [ 43 ]. Thus, the K p,uu,brain based on unbound concentration in plasma and brain ECF at steady state is a more clinically relevant measure to quantify drug transport at the BBB than rate measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system (CNS), PEPT2 can remove peptide/mimetic drugs from the cerebrospinal fluid to the plasma. PEPT2 is also responsible for the uptake of peptide/mimetic drugs from brain extracellular fluid into brain cells, which is important in regulating drug metabolism in the CNS [13][14][15]. PEPT2 protein consists of 729 amino acids, and the core molecular size is 81,940 Da.…”
Section: Discussionmentioning
confidence: 99%